Indirect effects of personality on high‐intensity drinking: The role of drinking motives. (23rd December 2022) - Bachrach, Rachel L.; Zhou, Agnes; Kumar, Lakshmi; Lyons, Greta; Skrzynski, Carillon J.; Creswell, Kasey G.
Abstract: Background: Researchers have long been interested in identifying risk factors for binge drinking behavior (4+/5+ drinks/occasion for females/males), but many studies have demonstrated that a substantial proportion of young adults are drinking at levels far beyond (often 2 to 3 times) the standard binge threshold. The consumption of such large quantities of alcohol, typically referred to as high‐intensity drinking (HID), can cause severe alcohol‐related problems, such as blackouts, unintended sexual experiences, and death. This study is the first to investigate whether personality is indirectly associated with the likelihood of HID via drinking motives in a large ( N = 999) sample of underage young adult drinkers. We hypothesized that trait neuroticism would be indirectly associated with the likelihood of HID via coping motives and that extraversion would be indirectly associated with the likelihood of HID via social and enhancement motives. Methods: To investigate these hypotheses, we used two archival data sets that recruited current underage (18‐ to 20‐year‐old) adult drinkers residing in the United States from online panel services. Participants completed self‐report survey items assessing constructs of interest. To investigate the role of drinking motives in the association between personality and HID, both the direct and indirect effects were calculated via three path analyses. Results: Findings revealed that neuroticism was partially indirectly associated with the likelihood of HID via coping motives ( b = 0.02, SE = 0.004, p < 0.01). In addition, extraversion was indirectly associated with the likelihood of HID via social ( b = 0.031, SE = 0.002, p < 0.01) and enhancement motives ( b = 0.01, SE = 0.002, p = 0.01). Conclusions: These findings are an initial step in examining the interplay among personality traits, drinking motives, and HID in underage drinkers and point to the need for longitudinal studies assessing these associations. Abstract : This study examined whether personality traits were indirectly associated with the likelihood of engaging in high‐intensity drinking (HID) via drinking motives in a large ( N = 999) sample of underage young adults. We found that neuroticism was partially indirectly related to HID likelihood through higher coping motives and extraversion was indirectly related to the likelihood of engaging in HID through higher social and enhancement motives. Findings provide initial steps toward examining the interplay between drinking motives, personality, and HID.